2004
DOI: 10.1159/000079832
|View full text |Cite
|
Sign up to set email alerts
|

Down Syndrome Candidate Region 1,a Downstream Target of VEGF, Participa tes in Endothelial Cell Migration and Angiogenesis

Abstract: Vascular endothelial growth factor (VEGF) is a principal stimulator of angiogenesis. However, the downstream targets of VEGF in endothelial cells (ECs) are not entirely clarified. Survey of downstream targets of VEGF in human ECs identified a number of genes, including Down syndrome candidate region 1 (DSCR1). Here, we confirmed the inducible expression of DSCR1 in ECs by Northern and Western blottings. Moreover, VEGF-stimulated induction of DSCR1 was blocked by anti-VEGF receptor-2 monoclonal antibody (mAb), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 60 publications
4
57
1
2
Order By: Relevance
“…Prior studies have demonstrated that DSCR1 inhibits endothelial cell proliferation, migration, and tube formation in vitro (14)(15)(16)(17). To confirm these findings and to compare the effects of DSCR1 to DSCR1-L1, HUVEC were infected with our retroviral construct containing the DSCR1 gene (pMX.myc.DSCR1).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Prior studies have demonstrated that DSCR1 inhibits endothelial cell proliferation, migration, and tube formation in vitro (14)(15)(16)(17). To confirm these findings and to compare the effects of DSCR1 to DSCR1-L1, HUVEC were infected with our retroviral construct containing the DSCR1 gene (pMX.myc.DSCR1).…”
Section: Resultsmentioning
confidence: 81%
“…Activated calcineurin dephosphorylates and induces the nuclear import of NF-ATc1 and NF-ATc2 in endothelial cells, resulting in the expression of angiogenesis-related genes including Cox-2 and E-selectin (11)(12)(13). Studies have demonstrated that DSCR1 is upregulated in response to VEGF in a calcineurin-dependent manner (14)(15)(16)(17), and that over-expression of DSCR1 in endothelial cells inhibits NF-AT translocation, NF-AT-mediated gene expression, and endothelial cell function (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Two of the enzymes in this group (MAOB and LAP3) are vasodilatory; monoamine oxidase metabolizes vasoactive amines to inactive forms and is found in high amounts within the preovulatory follicle and corpus luteum (Yoshimoto et al 1986) and LAP3 (also known as cysteine amino peptidase or oxitocinase) metabolizes oxytocin, vasopressin, and angiotensin III (Tsujimoto & Hattori 2005) and is a marker for malignant gynecological tumors (Ino et al 2004). The importance of VEGF in the angiogenic cascade that occurs in preovulatory luteinized follicles is well documented (Tamanini & De Ambrogi 2004) and DSCR1, a differentially expressed gene shown here, is an early response gene for VEGF (Iizuka et al 2004). PLANH1, the primary inhibitor of plasminogen activator that has been implicated in tumor growth and cellular remodeling (Stefansson et al 2003) and annexin a2 (ANXA2), a plasminogen-plasminogen activator co-receptor with angiogenic properties (Kim & Hajjar 2002), were also found to be differentially expressed.…”
Section: Genbankmentioning
confidence: 70%
“…Although RCAN1-4 is induced by an angiogenic factor VEGF, the overexpression of RCAN1-4 attenuated tube formation and cell cycle progression of ECs, thus inhibiting angiogenesis (70,93,94). When RCAN1 was knocked down, VEGF-stimulated migration of ECs and angiogenesis was also inhibited (95). In the previous model of cardiac hypertrophy and angiogenesis, RCAN1 deficiency inhibited calcineurin.…”
Section: Rcan1 and Non-neuronal Diseasesmentioning
confidence: 95%